Auditoría de gestión para maximizar la rentabilidad de la compañía de transportes Cándido Rada de la ciudad de Guaranda, provincia de Bolívar, periodo del 1 de enero al 31 de diciembre del 2021 - Manobanda Guamán, Mónica Consuelo (2022)
The Candida Rada Transport Company is an entity that provides urban and rural transport services in the city of Guaranda, the execution of the Management Audit allows evaluating, controlling and verifying the administrative and financial processes of the institution, which will facilitate achieving and objectively assess the structure of internal control. The present study constitutes a valuable tool because the phases of the Audit are used and executed, accessing the verification of the management of administrative procedures, thus knowing the real situation of the entity as well as its deficiencies or irregularities with the purpose of helping administration more efficient.